2019
DOI: 10.3892/ijo.2019.4898
|View full text |Cite
|
Sign up to set email alerts
|

UPLC‑MS/MS‑based metabolomic characterization and comparison of pancreatic adenocarcinoma tissues using formalin‑fixed, paraffin‑embedded and optimal cutting temperature‑embedded materials

Abstract: The purpose of the present study was to compare metabolites from formalin-fixed and paraffin-embedded (FFPE) pancreatic tissue blocks with those identified in optimal cutting temperature (OCT)-embedded pancreatic tissue blocks. Thus, ultra-performance liquid chromatograph-mass spectrometry/mass spectrometry-based metabolic profiling was performed in paired frozen (n=13) and FFPE (n=13) human pancreatic adenocarcinoma tissue samples, in addition to their benign counterparts. A total of 206 metabolites were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that lipids in fixed tissue differed from those in fresh‐frozen tissue based on ultraperformance liquid chromatography–mass spectrometry (UPLC–MS), gas chromatography–mass spectrometry (GC–MS), and MALDI‐IMS technologies 22,32,34,44–50 . Of these three technologies, MALDI‐IMS exhibited the maximal overlap of ions observed in PFA‐fixed and fresh‐frozen tissue 22–27 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that lipids in fixed tissue differed from those in fresh‐frozen tissue based on ultraperformance liquid chromatography–mass spectrometry (UPLC–MS), gas chromatography–mass spectrometry (GC–MS), and MALDI‐IMS technologies 22,32,34,44–50 . Of these three technologies, MALDI‐IMS exhibited the maximal overlap of ions observed in PFA‐fixed and fresh‐frozen tissue 22–27 .…”
Section: Introductionmentioning
confidence: 99%
“…23,43 Previous studies demonstrated that lipids in fixed tissue differed from those in fresh-frozen tissue based on UPLC-MS, GC-MS, and MALDI-IMS technologies. 22,32,34,[44][45][46][47][48][49][50] Of these three technologies, MALDI-IMS exhibited the maximal overlap of ions observed in paraformaldehyde-fixed and fresh-frozen tissue. [22][23][24][25][26][27] Regarding studies of retina, Ly et al 23 developed and compared lipid imaging by applying MALDI-IMS in fresh-frozen vs fixed mammalian (porcine) retina.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, formalin-fixed paraffin-embedded (FFPE) ovarian cancer tissue should be used for metabolomics testing because recurrent ascites are usually produced after surgical resection of the cancer tissue. FFPE tissue is not a routine metabolomics sample, but it has been reported that significant differential metabolites have been obtained from them (Arima et al, 2010;Feng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%